Entre a teoria e a prática: limites da aplicação da Ciência da Religião na produção dos livros didáticos de Ensino Religioso no Fundamental I - Silveira, Valeska Freman B. Freitas (2016)
This present work is a didactic transposition exercise of Science of Religion for Religious Education. Based on the theoretical and methodological assumptions of the Science of Religion, we analyzed four Collections of confessional Religious Education textbooks written to the elementary school, published in São Paulo, after 2000. The choice for the Science of Religion has been done, because this understand the religious as an object of knowledge, drawing on an epistemology that does not favor one religion over the others, because it is based on the principles of respect and appreciation of religious plurality, so we think that this could be applied in our confessional Religious Education Collections as it does not offend religious principles. Our goal was to identify the proximity between the theory of the Science of Religion and the contents of the textbooks of Religious Education. We researched if confessionality material compromised the knowledge of religions, it is threatening a proposal for Religious Education aimed at promoting a culture of peace and respect for plurality and religious tolerance. The analysis of Collections showed that the confessionality does not necessarily commits the understanding of religions, or a formation based on values of respect for differences. What sets the commitment to these issues is a coherent proposal by authors and publishers of the speeches and the material that actually produce. The relations between the Science of Religion theory and textbooks of Religious Education are still very fragile, we identified some opening initiatives for the acceptance of religious plurality without fear of considering it a threat to confessionality